Advances in Spark-Ignition Engines - Bozza, Fabio; De Bellis, Vincenzo; Malfi, Enrica (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on advanced techniques to reduce the impact of the transport sector and, more specifically, of Spark-Ignition (SI) Internal Combustion Engines (ICEs) on atmospheric air pollution and climate change. Hybrid vehicles represent the most suitable option for addressing these issues in the medium term, since hybridization allows us to overcome the major disadvantages of ICEs, electric units, and energy storage devices and merge their respective benefits. In this scenario, ICEs will remain the core component of automotive propulsion systems in the years to come. Of course, further efforts to improve the efficiency and reduce the pollutant and CO2 emissions of ICEs are necessary.